A Liver Cell Receptor for Uptake of Free Fatty Acids. (9th October 2014) - Unknown
Abstract : Free fatty acids travel through the circulation bound tightly to albumin. They are sequestered by a specific protein receptor in the plasma membrane of liver cells and internalized, to be taken up by the cytosolic fatty acid-binding protein.